A business strategy for eco-sustainability: some critical framework components. Issue 3 (14th March 2016) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – Sustainability has become one of the most important issues for businesses today. Growing concerns about environmental welfare has guaranteed that eco-sustainability is now high on many company agendas around the globe. The critical nature of sustainability is without question. Firms that fail to recognize this might be seriously jeopardizing competitiveness, growth and success in the longer term. Organizations face a pretty formidable challenge. The natural quest to attain economic goals must be balanced by the obligation to meet existing and future environmental and social responsibilities. Some companies can't be faulted for their efforts in this respect. Moves to reduce their carbon footprint and improve production systems are testimony to that. But in spite of such moves, natural resources continue to diminish as a result of business activities. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.